The Comparative Study on the Effect of Using Vocabulary Self-collection and Semantic Mapping Strategies on Students’ Reading Comprehension: The Vocabulary Self-collection and Semantic Mapping Strategies on Students’ Reading Comprehension - Zamrizal, Tengku; Darini, Rahma; Sawalluddin (Lembaga Anotero Scientific, 2022)
This study compared and examined the effects of vocabulary self-collection strategies and semantic mapping strategies on first-grade students at SMK N 1 Pangkalan Kerinci's reading comprehension skills. All of the SMK N 1 Pangkalan Kerinci first-year students made up the research's population. Two classes were picked for cluster random sampling: X1 Networking Computer Technique (28 students) served as experimental group 1 and X Accounting Major (28 students) served as experimental group 2. Using SPSS 21 version, the paired sample t-test and independent sample t-test formulas were applied to the data analysis. The results of the data analysis demonstrate that students' reading comprehension of narrative texts is significantly improved when they use vocabulary self-collection. With df 27 in significance levels of 5% and 1%, To is -6,669 more than Tt (2.06<-6,669>2, 79). Moreover, it is evident that the probability, or Sig. (2-tailed), is 0.000 less than 0.05 (0.000<0.05). Next, employing the Semantic Mapping Strategy has a noteworthy impact on an experimental group of students' reading comprehension of narrative texts. 2. With df 27 in significance levels of 5% and 1%, to is -10,708, which is more than tt (2.06<-10,708>2,79). Moreover, it is evident that the probability, or Sig. (2-tailed), is 0.000 less than 0.05 (0.000<0.05). That indicates that Ha is accepted and Ho is denied. The students in experimental group 2 can enhance their reading comprehension in narrative texts by 29,1%, according to the percentage of significant effect between the pre-test and post-test of the experimental class, as determined by checking for the effect size or eta-squared. Thus, it can be said that using the Semantic Map approach is superior to the Vocabulary Self-collection approach. Keyword: Reading comprehension, vocabulary self Collection, semantic mapping